Light off! movie onz! 2025 a night of entertainment and togetherness - Mohd Ruslan, Siti Zaharah; Othman, Norlida; Tengku Mohd Annuar, Tengku Faqihah Darwisyah; Mohamad Nazar, Nawal (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Cybermath Club organized Light Off! Movie Onz! on 11 May 2025 at Dewan Anjung Sri Perpatih, UiTM Cawangan Negeri Sembilan, Kampus Kuala Pilah, bringing together 107 participants and 18 committee members. With the theme “Art Class Vibe,” the program provided students with a relaxing and creative space to unwind from academic pressures while enjoying a movie together. The event not only offered entertainment but also encouraged social interaction, strengthened friendships, and promoted values such as empathy, responsibility, and creativity within the campus community.